The hobbit. The desolation of Smaug [videorecording (DVD)] - Jackson, Peter, 1961-; Blanchett, Cate, 1969-; McKellen, Ian; Nesbitt, James, 1965-; Bloom, Orlando, 1977-; Fry, Stephen, 1957-; Lilly, Evangeline, 1979-; Stott, Ken, 1955-; Cumberbatch, Benedict, 1976-; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (2013)
Bilbo Baggins continues on in his journey with the wizard Gandalf and thirteen dwarves, led by Thorin Oakenshield, on an epic quest to reclaim their lost Dwarf Kingdom of Erebor.